Biomechanical evaluation of adjunctive cerclage wire fixation for the prevention of periprosthetic femur fractures using cementless press-fit total hip replacement. (August 2016) - Christopher, Scott A.; Kim, Stanley E.; Roe, Simon; Pozzi, Antonio
Highlights: An adjunctive proximal double loop cerclage wire increased the axial and torsional loads to failure in BFX implanted stems. The most common periprosthetic femoral fractures failed with a Vancouver class B2 or B1 fracture. An adjunctive double loop cerclage wire may aid in the prevention of periprosthetic fractures associated with BFX. Multiple cerclage wires may be indicated in dogs at high risk of periprosthetic fractures. Abstract: Periprosthetic femoral fractures are a common complication associated with cementless press-fit total hip arthroplasty. The use of prophylactic cerclage wire fixation has been advocated to reduce this complication. The objective of this study was to evaluate whether a double loop cerclage wire, used as adjunctive fixation, increased the peak torsional load to failure in femora implanted with press-fit cementless stems. Peak torsional load to failure was compared between femora without adjunctive fixation and femora receiving a 1 mm double loop cerclage wire placed proximally to the lesser trochanter. Femora treated with adjunctive cerclage wire fixation failed at 20% greater peak torque ( P = 0.0001). In conclusion, a double loop cerclage wire may aid in the prevention of periprosthetic fractures associated with press-fit cementless femoral stems.